The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.chemmater.1c01992
|View full text |Cite
|
Sign up to set email alerts
|

Searching Ternary Oxides and Chalcogenides as Positive Electrodes for Calcium Batteries

Abstract: The identification of alternatives to the lithium-ion battery architecture remains a crucial priority in the diversification of energy storage technologies. Accompanied by the low reduction potential of Ca2+/Ca, −2.87 V vs standard hydrogen electrode, metal-anode-based rechargeable calcium (Ca) batteries appear competitive in terms of energy densities. However, the development of Ca batteries lacks high-energy-density intercalation cathode materials. Using first-principles methodologies, we screen a large chem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 89 publications
0
22
0
Order By: Relevance
“…If we qualitatively assume that ∼30 meV/atom is the (vibrational) entropic stabilization accessible at room temperature (see the blue line in the color bar of Figure a), our results suggest that only NaSICONs with low Si (0 < i < 0.5) and low S (0 < i < 1) contents might be experimentally accessible for specific ranges of Na concentrations.…”
Section: Rational Design Of High-energy Density Nasicon Electrodesmentioning
confidence: 76%
“…If we qualitatively assume that ∼30 meV/atom is the (vibrational) entropic stabilization accessible at room temperature (see the blue line in the color bar of Figure a), our results suggest that only NaSICONs with low Si (0 < i < 0.5) and low S (0 < i < 1) contents might be experimentally accessible for specific ranges of Na concentrations.…”
Section: Rational Design Of High-energy Density Nasicon Electrodesmentioning
confidence: 76%
“…Note that calculating the activation barriers for Ca migration (for example, using the DFT-based nudged elastic band method 85 ) are not trivial within the NaSICON framework. Indeed, some of us have recently completed a set of mobility calculations on Ca cathodes, 28 as well as NaSICONs relevant for Na-ion batteries 86 where we had to endure significant convergence difficulties and computational costs in our calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lu et al reported two promising Ca-cathode compositions, via a DFTbased screening procedure that included average voltages, charge neutrality, thermodynamic stability, and activation barriers, namely post-spinel-CaV2O4 and layered-CaNb2O4. 28 While recent experiments indicate promise on reversible Ca intercalation in CaV2O4, further optimization of the electrode framework is required. 29 In the chemical space of sulfide cathodes, Palacin and co-workers have explored the electrochemical activity of Ca in TiS2 for a variety of electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Computation methods can aid in identifying potential materials as cathodes either by screening a pool of existing candidates that has been already tested for well-established LIBs or by predicting new possible compounds by assessing the combination of the different stoichiometry of various elements. Theoretical calculations predicted that MoO 2 and spinel-type CaV 2 O 4 and CaNb 2 O 4 can serve as high-capacity cathodes for CIBs. , The maximum capacity of Ca-intercalated MoO 2 or Ca 3 MoO 2 is estimated to be 1256 mAh g –1 with an average working potential of 0.35 V. According to NEB calculations, the low Ca diffusion barrier (∼0.22 eV) is expected to result in facile Ca-ion intercalation in MoO 2 . Crystal structures of CaV 2 O 4 and CaNb 2 O 4 and the possible Ca-diffusion paths drawn from NEB calculations suggest migration energy paths of 654 and 785 meV (Figure a,b).…”
Section: Computational and Experimental Analyses For Cathodes Of Cibs...mentioning
confidence: 99%
“…assessing the combination of the different stoichiometry of various elements. Theoretical calculations predicted that MoO 2 and spinel-type CaV 2 O 4 and CaNb 2 O 4 can serve as highcapacity cathodes for CIBs 108,109. The maximum capacity of Caintercalated MoO 2 or Ca 3 MoO 2 is estimated to be 1256 mAh g −1 with an average working potential of 0.35 V. According to NEB calculations, the low Ca diffusion barrier (∼0.22 eV) is expected to result in facile Ca-ion intercalation in MoO 2 .…”
mentioning
confidence: 99%